The Influence of Early Modern Theories of Governance on the Corporeal Images of the 1608 King Lear Quarto - Mudriczki, Judit (FOCUS: Papers in English Literary and Cultural Studies, 2014)
Focusing on the figure of the monarch, Shakespeare’s King Lear reflects the nature of kingship from a delicately refined Renaissance point of view. Serving as a dramatized version of the contemporaneous genre “mirror of governance,” the 1608 chronicle history thematizes such central concerns of power as responsibility, inheritance, and flattery, which were particularly topical in the early Jacobean era. While the dramatic structure of the play strongly resembles that of political moralities (see Bradley 226, Mack 58, and Potter 152), the poetic text draws heavily upon powerful images referring to the human body as a whole and also to its parts (see Spurgeon 339, Hillman 81). Although today scholars tend to turn to the references concerning Lear’s physical body, the author of this paper sides with critics including Mary Axton and Albert Rolls, whose studies link King Lear with Renaissance p olitical concepts based on the analogy between the state and the human body. In what follows, the paper first summarizes the presence of the corporeal images in contemporaneous governance theories, and then it shows how they determine historical readings of the 1608 King Lear quarto.